2023
DOI: 10.1007/s40122-023-00542-w
|View full text |Cite
|
Sign up to set email alerts
|

Arts Therapy and Its Implications in Chronic Pain Management: A Narrative Review

Jaroslava Raudenská,
Veronika Šteinerová,
Šárka Vodičková
et al.

Abstract: Chronic nonmalignant pain is recognized as a complex, dynamic, phenomenological interplay between biological, psychological, and social factors that are individual to the person suffering from it. Therefore, its management and treatment ought to entail the individual’s biopsychosocial aspects that are often addressed by collaborative, inter/multidisciplinary multimodal care, as there is no biologic treatment. In an effort to enhance inter/multidisciplinary multimodal care, a narrative review of arts therapy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(263 reference statements)
0
1
0
Order By: Relevance
“…Patients used drawing activities as an opportunity to modify their perceptions of their pain and to ‘take control’ over their pain, which in turn led to better coping abilities and pain reduction [ 36 ]. A similar scoping review looked at the effect of art therapy in an adult chronic pain populations and found 14 studies that demonstrated positive outcomes in pain reduction [ 37 ]. The main findings of the adult scoping review are that through art therapy-based interventions, patients can learn to draw their focus away from their current levels of pain and express themselves in a meaningful way, improving their psychosocial and physical well-being [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients used drawing activities as an opportunity to modify their perceptions of their pain and to ‘take control’ over their pain, which in turn led to better coping abilities and pain reduction [ 36 ]. A similar scoping review looked at the effect of art therapy in an adult chronic pain populations and found 14 studies that demonstrated positive outcomes in pain reduction [ 37 ]. The main findings of the adult scoping review are that through art therapy-based interventions, patients can learn to draw their focus away from their current levels of pain and express themselves in a meaningful way, improving their psychosocial and physical well-being [ 37 ].…”
Section: Discussionmentioning
confidence: 99%